PENGENALAN LITERASI KEUANGAN DAN PENGELOLAAN KEUANGAN KELUARGA BAGI IBU-IBU RUMAH TANGGA (PADA KELOMPOK PKK KECAMATAN SOKARAJA KIDUL) - Tiyas Ayu Ningrum Anggita Putri Perdani; Muftikhatur Rohmah; Intania Fajar Andini, (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
This examines financial literacy among housewives in the PKK group of Sokaraja Kidul District, which remains low according to OJK data from 2022. The research aimed to analyze financial literacy levels and develop effective educational models aligned with local socio-economic characteristics. The study employed a qualitative approach with triangulation techniques through in-depth interviews, focus group discussions, and participatory observation of 45 housewives. The financial literacy socialization program was conducted in four main sessions covering basic concept introduction, budgeting techniques, saving and investment strategies, and financial recording application usage. Results showed significant improvement in financial literacy levels from an average score of 45 to 72. The andragogical approach combining various learning methods effectively accommodated participants' diverse learning styles. In conclusion, empowering housewives as agents of change in family financial management contributes to improving the economic welfare of families and communities.